Cardiac dysfunctions in children with drug-resistant epilepsy - Sridech, Watthana; Intamul, Kamonchanok; Saengsin, Kwannapas; Wiwattanadittakul, Nattarujee; Sittiwangkul, Rekwan; Katanyuwong, Kamornwan; Silvilairat, Suchaya; Sanguansermsri, Chinnuwat (Frontiers in Neurology, 2024)
Objective There were reports of cardiac dysfunction that led to sudden unexpected death in epilepsy (SUDEP) in patients with epilepsy. Early detection of cardiac dysfunction can lead to early management to prevent sudden cardiac death in these patients. The objective of our study is to assess cardiac functions in children with drug-resistant epilepsy (DRE) compared with the normal population by using a standard echocardiogram (SE), tissue Doppler imaging (TDI) and myocardial strain evaluations (MSE). Method Twenty-seven children who have been diagnosed with DRE based on the International League against Epilepsy (ILAE) were included in the study, along with 27 children whose ages match those of the normal control group. Results Seventeen children, median age 12 years old, were using more than four anti-seizure medications. Structural brain lesions were the most common cause of epilepsy, 55.6% (15). Generalized tonic–clonic seizures were the most common seizure type, 55.6% (15). Children with DRE had a lower early mitral valve E wave inflow velocity compared with the control group (p < 0.05). They also had lowered early diastolic velocities (e′) and myocardial performance index (MPI) when compared with the control group (p < 0.05). There was a statistically significant difference in left ventricular myocardial strain in children with DRE, with an average of −21.1 (IQR −23.5 and −19.4) and control, −25.5 (IQR −27.3 and −24.2). Significance Children with DRE have an impairment of left ventricular diastolic function and myocardial strain, which could indicate decreased myocardial deformation and contraction compared with controls. These cardiological assessments can be used to evaluate children with DRE for early diagnosis and management of their cardiac dysfunction.